2019
DOI: 10.35840/2631-5076/9230
|View full text |Cite|
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Metal Injection Molding HK30 Stainless Steel Sintered in N2 and Ar Atmosphere

Abstract: The effects of different sintering atmospheres (nitrogen and argon) on the densification, microstructure, and mechanical properties of HK30 stainless steel were studied. Compared with those of the samples sintered in Ar, sintered samples in N 2 had a lower density and higher N content. Some of the N atoms dissolved into the austenite matrix, and others were combined with metal atoms to be precipitated along the grain boundaries. Samples sintered in N 2 had a higher hardness than those in Ar. The hardness decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The influence of the sintering atmosphere on the densification properties of HK30 materials was studied. 67 The results showed that the density was lower when sintered with N 2 than with Ar. However, HK30 parts sintered in N 2 had a higher hardness and tensile strength than those sintered in Ar.…”
Section: Factors Related To the Properties Of Sintered Stainless-ste...mentioning
confidence: 96%
See 2 more Smart Citations
“…The influence of the sintering atmosphere on the densification properties of HK30 materials was studied. 67 The results showed that the density was lower when sintered with N 2 than with Ar. However, HK30 parts sintered in N 2 had a higher hardness and tensile strength than those sintered in Ar.…”
Section: Factors Related To the Properties Of Sintered Stainless-ste...mentioning
confidence: 96%
“…This impedes the diffusion of iron or chromium and restricts the densification rate. 67 The phase diagram of 17-4PH with a carbon content of less than 0.04 wt.% indicates that the liquid phase occurs slightly above 1360 °C (see Figure 12). 7 The formation of δ-ferrite during high sintering temperatures and the development of the microstructure during sintering are summarized in the following structures: ferrite (α); austenite (γ); and γ + δ-ferrite.…”
Section: Particle Size and Carbon Contentmentioning
confidence: 99%
See 1 more Smart Citation